CARD9 Signaling, Inflammation, and Diseases - Liu, Xuanyou; Jiang, Bimei; Hao, Hong; Liu, Zhenguo (Frontiers in Immunology, 2022)
Caspase-recruitment domain 9 (CARD9) protein is expressed in many cells especially in immune cells, and is critically involved in the function of the innate and adaptive immune systems through extensive interactions between CARD9 and other signaling molecules including NF-κB and MAPK. CARD9-mediated signaling plays a central role in regulating inflammatory responses and oxidative stress through the productions of important cytokines and chemokines. Abnormalities of CARD9 and CARD9 signaling or CARD9 mutations or polymorphism are associated with a variety of pathological conditions including infections, inflammation, and autoimmune disorders. This review focuses on the function of CARD9 and CARD9-mediated signaling pathways, as well as interactions with other important signaling molecules in different cell types and the relations to specific disease conditions including inflammatory diseases, infections, tumorigenesis, and cardiovascular pathologies.